Burden of knee osteoarthritis in China and globally from 1992 to 2021, and projections to 2030: a systematic analysis from the Global Burden of Disease Study 2021 - Lv, Yueming; Sui, Liang; Lv, Hao; Zheng, Jiacheng; Feng, Huichao; Jing, Fujie (Frontiers in Public Health, 2025)
BackgroundKnee osteoarthritis (KOA) is primarily characterized by joint pain and dysfunction, and KOA has increasingly emerged as a public health concern in China and globally. This study aims to utilize data from the Global Burden of Disease (GBD) 2021 to summarize the disease burden of KOA in China and globally from 1992 to 2021, while also predicting the disease burden in 2030.MethodsUsing data from the GBD 2021 study, we compared and described the burden of KOA in China and globally. Joinpoint regression was applied to assess long-term trends in the burden of KOA based on GBD 2021 data. The impact of population growth, aging, and epidemiological trends on the burden of KOA was examined through decomposition analysis. Additionally, an age-period-cohort analysis (APC) was conducted to assess the effects of age, period, and cohort on the burden of KOA in China. Finally, we predicted the burden of KOA in 2030 using the Bayesian age-period-cohort (BAPC) and Norpred models.ResultsIn 2021, the number of patients with KOA in China was 10,957,472, reflecting an increase of 157.15% compared to 1992. Similarly, the incidence of KOA in China for the same year was 8,512,396, representing a rise of 123.45% since 1992. The and Years lived of disabled (YLDs) rate for KOA in China was 249.81 per 100,000 population, which is 116.44% higher than the rate observed in 1992. In 2021, the prevalence of KOA increased with age. Female exhibited higher estimates of prevalence, incidence, and YLDs than male across all age groups. Joinpoint regression analysis revealed fluctuating upward trends in prevalence, incidence, and YLDs, from 1992 to 2021. Decomposition analysis identified population growth as the primary driver of increased prevalence, incidence, and YLDs, particularly among female. Projections indicate that the number of KOA YLDs in China will continue to rise, potentially reaching a peak by 2030.ConclusionThe disease burden of KOA in China remains significant, necessitating increased attention, particularly for female and the middle-aged and older adult populations, in order to develop more targeted preventive measures.